The evolution of psychology in the organizational sector - Saldanha , Dayanne Cavalcante; Conceição , Marcio Luz da (Seven Editora, 2023)
This paper aims to study the role of psychology in the organizational world, knowing its principle and all its evolution. It is known that in the beginning, psychology within companies was used only to evaluate criteria for recruiting employees. Nowadays, psychology is much more involved with the well-being of employees, working holistically with the team, strengthening ties, and, consequently, increasing productivity, as motivated and happy employees yield much more to companies. As part of this motivation, the inclusion of diversities in the job market has been increasing, bringing more opportunities and qualifications to the corporation. Qualitative bibliographic research was carried out to collect the data in this article, and the conclusion was that as the human being is constantly evolving, psychology is fundamental to understanding these changes in social profiles and adapting companies to them, increasingly integrating society. DOI:https://doi.org/10.56238/alookdevelopv1-171